The biosynthetic pathway of 2-azahypoxanthine in fairy-ring forming fungus - Suzuki, Tomohiro; Yamamoto, Naoki; Choi, Jae-Hoon; Takano, Tomoyuki; Sasaki, Yohei; Terashima, Yurika; Ito, Akinobu; Dohra, Hideo; Hirai, Hirofumi; Nakamura, Yukino; Yano, Kentaro; Kawagishi, Hirokazu (Springer, 2016)
“Fairy rings” resulting from fungus-stimulated plant growth occur all over the world. In 2010, 2-azahypoxanthine (AHX) from a fungus Lepista sordida was identified as the “fairy” that stimulates plant growth. Furthermore, 2-aza-8-oxohypoxanthine (AOH) was isolated as a common metabolite of AHX in plants, and the endogenous existence of AHX and AOH in plants was proved. The structure of AHX allowed us to hypothesize that AHX was derived from 5-aminoimidazole-4-carboxamide ribonucleotide (AICAR). Thus, we performed a feeding experiment that supplied AICAR to L. sordida. Consumption of AICAR and accumulation of AHX were observed after feeding. The mycelia extract had enzymatic activity of adenine/5-aminoimidazole-4-carboxamide phosphoribosyltransferase (APRT). APRT gene of L. sordida revealed its structural characteristics in homology modeling and showed transcriptional enhancement after feeding. These results support that AHX was synthesized from AICAR and AHX biosynthesis was transcriptionally controlled by AICAR, indicating the presence of novel purine metabolic pathway in L. sordida.